PENERPAN PETRI-NET PADA MODEL GERAKAN BERJALAN TROTTING ROBOT BERKAKI EMPAT (QUADRUPED) - Tony Yulianto (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2015)
Nowadays many robots has produced not just on a few scale, but also on large for helping human on doing task everyday corresponding the function. By the way, the function can be good functionate if the components, which support to the robot, can be good functionate, too, like the other one is robot walked way movement. Here, we look on four legs of robot walked movement using trotting, because we can find this nowadays and the trouble is kind than robot walked movement with two legs. On this case, we will use max-plus algebra to solve this problem to get robot walked way model on trotting which is like what we want.